PENELITIAN LAPISAN AIR TANAH DENGAN METOD GEOLOGI PERMUKAAN, GAYA BERAT DAN GEOLISTRIK DI CEKUNGAN BANDUNG TIMUR - Panjaitan, Saultan (Pusat Survei Geologi, 2007)
Bouguer anomaly of 20 to 44 mgal are interpreted as igneous rocks and volcanic sediments. On the other hand, low Bouguer anomaly of 8 mgal to 20 mgal reflect the Bandung Basin. The Bandung Basin can be divided into two smaller basins, they are the Western Bandung Basin and the Eastern Bandung Basin. The Eastern Bandung Basin is marked by Bouguer anomaly of 10 mgal. The two smaller basins are separated by a high Bouguer anomaly of 30 mgal trending from south of Mount Malabar to the north of Ujungberung subdistrict. The thickness of Quaternary layers in the Eastern Bandung Basin at gravity profile is between 400 - 1000 m. This interpretation is supported by the resistivity value of ? around 551 ohm. Groundwater layers can be groupped into two parts: the shallow and deep groundwater. Shallow groundwater is found at the depth of 13 - 35 m with ? 8 - 13.2 ohm metres. Deep groundwater is located at depth of 70 m with ? 2.8 - 8.5 ohm metres. The shallow and deep groundwater layers are separated one from the other by impermeable rocks with ? value varies up to 551 ohm metres.